Managerial Innovation Incorporated into the Management Control System: A Case Study in A Metallurgy Sector Organization - Pletsch, Caroline Sulzbach; Silva, Marcia Zanievicz (Advances in Scientific and Applied Accounting, 2024)
Objective: The study aims to characterize how managerial innovation was incorporated into the Management Control System (MCS) in the organization under study in an organization in the metallurgy sector. Method: This is a qualitative, descriptive study and case study in an organization listed on B3, in the metallurgy sector. Management innovation emerged from the case study, being represented by a new management model. Data collection took place through interviews, documents and observation. Content analysis was used to analyze the data, with the help of Nvivo Software. Results: It appears that the organization has focused on new control systems, accounting and management information, which allow agility and assertiveness in decision making. The managerial practice of defining and monitoring indicators and structuring internal procedures requires a management process focused on employee performance, strategic planning and budget. Information technology enables systems that facilitate operations and processes. Changes in the cost management system improved analysis and reduced costs, favoring the creation of new product lines and new markets. These actions allow external transparency, which is reflected in new partnerships and strengthening of external relations. Contributions: The insights generated by the managerial innovation incorporated into the SCG allow companies to define and monitor performance indicators, use internal procedures, seek agility and assertiveness in decision-making, value and recognize the performance of employees, invest in strategic planning and budget, in people management, KPIs Dashboard, new partnerships and strengthening relationships with companies, customers, suppliers.